Company Bankruptcy in Poland and Other European Union Countries in the Period 2005–2014 - Szmal-Kaptur, Jagoda (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
Bankruptcy is an inherent element of any market economy and can affect any company. The number of bankruptcies in Poland in comparison to other EU countries in the period 2005-2014 is analysed. Additionally, this study evaluates the bankruptcy process among Member States on the basis of such assessment indicators including: time required to liquidate the company, the cost and recovery rate. The research hypothesis assumes that the course of the bankruptcy process depends on the quality of insolvency law. Analysis of the data revealed that in Poland the course of the bankruptcy process is long and expensive, while the recovery rate is low. Poland’s inefficient bankruptcy process discourages enterprises from choosing the path of formal exit from the market and places Poland far down the ranking of insolvency systems in Europe.